Massive Pleural Effusion in an 18-Year-Old Girl with Ewing Sarcoma - Cengiz Özge; Mukadder Çalikoglu; Leyla Cinel; F Demir Apaydin; Eylem S Özgür (Canadian Respiratory Journal)
Ewing sarcoma is a bone tumour that commonly appears between ages five and 10 in the diaphysis of the long bones and predominantly presents with pain and swelling. The case of an 18-year-old girl who presented with back pain, cough, dyspnea, weakness and fever is described. Chest radiograph showed a homogenous density in the middle and inferior zones of the right hemithorax. Thoracic computed tomography revealed a diffuse pleural effusion and a 6.99 cmx4.45 cm solid mass composed of lobulated, small cystic lesions and calcifications in the right hemithorax. Biochemical analysis of pleural fluid showed hemorrhagic effusion and exudate. A pleural needle biopsy demonstrated solid uniform tumour cells with narrowed cytoplasm, round nuclei and uncertain nucleoli. All of the tumour cell cytoplasms stained with CD99. The pathological examination supported Ewing sarcoma. Three-phase Tc-99m methylene diphosphonate scintigraphy of the whole body showed pathological tracer uptake in a broad area of the eighth costal bone and in smaller areas of the ninth and 10th costal bones. This case is reported because Ewing sarcoma is a rare cause of pleural effusion in clinical practice among younger adults.